Unmasking the frenetic guise of infidelity case among Indonesian artists on CNN news media: Critical discourse analysis - Rakhmawati, Ani; Gumelar, Naufal Allam (Journal of Applied Studies in Language, 2024)
Infidelity cases are one of the everlasting problems for human life. It is becoming thought provoking news for reader when it occurs around celebrities’ life. This study aims to investigate the infidelity case published on CNN Indonesia media in 2023, particularly of the victim's personal position and readers' responses to news texts. The data collection technique used were by reading and recording data. Data collected was analyzed using Sara Mills' perspective analysis model of critical discourse analysis to investigate subject-object position and writer-reader position. The reader's position was examined in three stages: (1) the reader's position as a reader of a news text, (2) the reader's position as seeing himself/herself in a news text, and (3) the reader identifies within the group on the news text. Based on the subject-object position in the news, it was discovered that these news texts of the affair cases positioned the female victim as both subject and object, while another news text positioned the husband as the subject and the wife as the object. Accordingly, based on the subject-object position depicted on the news, the reader engagement of interesting news material increases news media ratings. The results of this study revealed that celebrity news regarding affair and infidelity cases are not only reported by journalists but disclosed privately through an Instagram account. This research shows that infidelity news in the mass media is caused and influenced by readers and perpetrators of actions themselves